Monetary Policy Rules in an Open Economy with Heuristics: Which Model Is Best?. Issue 9 (1st September 2016) - Yeh, Kuo-chun
ABSTRACT: The choices of policy targets and the formation of agents' expectation have been critical issues for reconsidering monetary policy management since 2008. The purpose of this article is to evaluate macroeconomic stability in a New Keynesian open economy in which agents experience cognitive limitations. The (im)perfect credibility of various monetary policies (e.g., a Taylor-type rule, strict domestic inflation targeting, strict CPI inflation targeting, exchange rate peg) may lead agents to react according to their expectation rules, and then create various degrees of booms and busts in output and inflation. Therefore, relaxation of the rational expectation hypothesis has potential consequences for policy designs. Our simulations confirm that the business cycles induced by animal spirits are enhanced by strict inflation targeting. Furthermore, a Taylor-type (CPI or domestic inflation) rule or a credible exchange rate pegging system can improve social welfare and stability in an open economy.